Pengembangan Bahan Ajar Bahasa Inggris Berbasis Analisis Kebutuhan Dunia Kerja - Noviaty, Putu Shinta; Lestari, Eka Ayu Purnama; Trisnadewi, Komang (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
Time development will affect the changing needs of graduates. Using teaching materials as one of the factors supporting the learning process is an absolute thing to do so that learning becomes directed. Therefore, it is necessary to conduct this research to prepare highly competitive human resources. This research is a development that aims to produce materials oriented towards analyzing the needs of graduate users. The ADDIE method includes analysis, design, development, implementation, and evaluation. It was chosen as the basis for developing teaching materials for STMIK STIKOM Indonesia students on Information Technology. The analysis stage is the stage carried out to describe what the learner will learn. Next is the design stage. The purpose of learning, strategies, learning resources, tests are designed. It becomes a supporting factor for the learning process. Development is the next stage where the process of making materials is carried out according to a predetermined design. The next stage is implementation. Submission of material by the results of the development is carried out at this stage. The last stage is the evaluation stage. The revision process is carried out at this stage to assess the designed learning program.Time development will affect the changing needs of graduates. Using teaching materials as one of the factors supporting the learning process is an absolute thing to do so that learning becomes directed. Therefore, it is necessary to conduct this research to prepare highly competitive human resources. This research is a development that aims to produce materials oriented towards analyzing the needs of graduate users. The ADDIE method includes analysis, design, development, implementation, and evaluation. It was chosen as the basis for developing teaching materials for STMIK STIKOM Indonesia students on Information Technology. The analysis stage is the stage carried out to describe what the learner will learn. Next is the design stage. The purpose of learning, strategies, learning resources, tests are designed. It becomes a supporting factor for the learning process. Development is the next stage where the process of making materials is carried out according to a predetermined design. The next stage is implementation. Submission of material by the results of the development is carried out at this stage. The last stage is the evaluation stage. The revision process is carried out at this stage to assess the designed learning program.